Family Social Support and Career Adaptability in Students of Faculty of Psychology, Satya Wacana Salatiga Christian University - Cantikasri Hastuti; Sutarto Wijono (Journal of Social Research, 2023)
Final year students who experience the transition from the world of education to the world of work (school-to-work) is a big challenge that all students must face. Final year students still need to prepare many things related to the career path they will take. However, some of the final year students are still indecisive and unprepared in determining their careers after graduating from college, so they need to prepare themselves to be able to adjust when entering the world of work by having career adaptability. Therefore, this study aims to determine the relationship between family social support and career adaptability in college students. The type of research method used is quantitative method with correlational design. The participants involved in this study were 81 students of the Faculty of Psychology, Satya Wacana Christian University class of 2019. The measurement scale used is a family social support scale (Social Provisions Scale Chapter) and a career adaptability scale (Career Adapt Abilities Scale). Based on the results of the Pearson product moment correlation test, r = 0.556 was obtained with sig. = 0.000 (p<0.01). Based on the results of this study, it can be concluded that there is a significant positive relationship between family social support and career adaptability in college students. Thus, the hypothesis proposed in this study can be accepted. The results of this study can help individuals overcome the obstacles experienced and prepare individuals to overcome unexpected situations that arise in facing the transition from education to the world of work. The results of this study indicate that the higher the family social support, the higher the level of career adaptability in college students.